A new species of Cynopotamus Valenciennes, 1849 (Characiformes, Characidae) with a key to the species of the genus - Menezes, Naércio A. (Zootaxa, 2007)
Cynopotamus xinguano n. sp. is described from middle-upper tributaries of rio Xingu basin. Among the known species of the genus (Menezes, 1976, 1987) it is more similar to C. essequibensis Eigenmann from which it differs by having more developed gill-rakers on first branchial arch and a different arrangement of muscles around muscular hiatus of pseudotympanum. A new key for species identification is provided.